Origin of the Dufek layered mafic intrusion and the Ferrar igneous province, Antarctica: A geochemical approach. - Zhou, Pinbo (2001)
A systematic geochemical investigation has been carried out on the Dufek layered mafic intrusion in Antarctica in order to understand the petrogenesis of the intrusion and the origin of the Ferrar igneous group to which the intrusion belongs. For the ∼8-km thick Dufek intrusion, a new two-fraction baddeleyite U-Pb age of 182.1 +/- 0.8 Ma has been determined for the Walker Anorthosite, the lowest layer in the ∼3.5 km of stratigraphic section exposed. A silicic dike cutting through the top part of the Dufek Massif section yields a zircon U-Pb age of 181.2 +/- 0.4 Ma, which is interpreted to record the waning stages of the magmatism and thus the minimum crystallization age of the intrusion. Sr-Nd-Pb isotopic compositions of mineral separates from the Dufek layered mafic intrusion have been analyzed. The data show that the crustal contamination operates mainly at the roof zone of the magma chamber. The gradual increase of initial Sr isotopic ratios toward the top of the intrusion indicates that there might exist a vertical Sr isotopic gradient at magma chamber when magma solidified. Irregular isotopic variation of the mineral separates across various rock layers and isotopic disequilibrium between mineral phases in the same rock layer imply extensive migration of crystals during magma differentiation. Crystal settling/floating and the related magma processes, such as slumping, roof collapse and density currents, are believed to be the main mechanisms for magma to differentiate and to redistribute chemical species in forming a stratified magma chamber and eventually to form the macro layering series in the intrusion. Modeling on the isotopic and major- and trace-element data of the Dufek intrusion and the nearby dikes/sills, as well as those of other Ferrar rocks has led us to conclude that Ferrar magmatism was originated in the lithospheric mantle where extensive mantle melting occurred as a result of interaction between asthenosphere-derived melts/fluids and the lithospheric mantle that contained abundant old ...